Resistensi dalam Literasi - Rohmatika, Idha Ismalia; Sulaeman, Otong (Indonesia Center for Middle East Studies, 2022)
Palestine is the only nation in the world still experiencing physical occupation. In 1948, Israel was founded on the land of the Palestinian people by expelling the population and occupying the land they left behind. In facing the colonial situation, the Palestinians carried out resistance in various ways, including cultural resistance, and one of the models was artistic imitation or mimicry. This article aims to find the pattern of mimicry that occurs in Palestine using the postcolonial approach of Edward Said and the mimicry theory introduced by Homi Bhabha. This article concludes that some Palestinians consciously imitate Jewish and Israeli culture and literacy. The imitation effort was carried out as part of a strategy to gain independence.